Evidence for two heat-stable enterotoxins produced by enterotoxigenic Escherichia coli. - Kapitany, R A (1979)
Heat-stable enterotoxins from a bovine and porcine strain of Escherichia coli were isolated and showed significant differences in amino acid composition and heat stability.